INELIGIBILITY AND THE CRITICAL APPROACH TO THE RIGHT TO RE-ELECTION (REMUNOM, 2023)
The critical discussion about re-election in Brazil focuses on the possible impacts of this right on the political system. One of the main concerns is the possibility that re-election will lead to an excessive concentration of power in the hands of political leaders. When allowing a president, governor or mayor to be re-elected for a second consecutive term, questions then arise, casting doubt on the checks and balances mechanisms, which are fundamental in a democracy. Another important analysis is the perpetuation of political oligarchies, which means that specific families or groups can dominate politics over generations, making it difficult to include new voices and renew politics. The excessive focus on seeking re-election to the detriment of longterm decisions, the potential for abuse of public resources and the deterioration of the image of politics due to polarized campaigns. It is worth mentioning that the search for re-election can lead to a potentially inappropriate use of public resources and the manipulation of elections by incumbents, who seek to maintain power at any cost.